Development of Worksheets for Biology High School Student-Based On Critical Thinking Skills on the Concept of Biodiversity - Amalia Mardhatillah; Muhammad Zaini; Aminuddin Prahatama Putra (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2020)
Critical thinking skills are one of the cognitive skills that are necessary for learners in the 21st century. The government implements the 2013 curriculum to improve learners ' critical thinking skills with one of its components of teaching materials in a student's worksheet (LKPD). The problem is that the use of LKPD is still lacking in facilitating learners ' critical thinking skills. This research aims to develop the LKPD on the concept of biodiversity that is valid, practical, and effective. The research methods used are Tessmer design, which includes: expert review, one-to-one evaluation, and small group evaluation. The LKPD structure was developed referring to Daryanto & Dwicahyono and critical thinking skills referring to the Facione 1990. Subject validation includes three experts, one to one evaluation subjects are three learners of class X SMA, and a small group evaluation subject is six students of class X SMA. The results showed that the effectiveness of expectations seen from the assessment of critical thinking skills of learners in completing the LKPD belongs to a very good category.AbstrakKeterampilan berpikir kritis merupakan salah satu keterampilan kognitif yang perlu dimiliki peserta didik pada abad ke-21. Pemerintah menerapkan kurikulum 2013 untuk meningkatkan keterampilan berpikir kritis peserta didik dengan salah satu komponennya bahan ajar berupa Lembar Kerja Peserta Didik (LKPD). Permasalahan yang ada adalah penggunaan LKPD masih kurang dalam memfasilitasi keterampilan berpikir kritis peserta didik. Penelitian ini bertujuan untuk mengembangkan LKPD pada konsep keanekaragaman hayati yang valid, praktis, dan efektif. Metode penelitian yang digunakan adalah desain Tessmer, yang meliputi: 1) expert review; 2) one-to-one evaluation; dan 3) small group evaluation. Struktur LKPD yang dikembangkan mengacu pada Daryanto & Dwicahyono dan keterampilan berpikir kritis mengacu pada Facione 1990. Subjek validasi meliputi 3 orang ahli, subjek uji perorangan adalah 3 orang peserta didik kelas X SMA, dan subjek uji kelompok kecil adalah 6 orang peserta didik kelas X SMA. Hasil penelitian menunjukkan bahwa keefektifan harapan yang dilihat dari penilaian keterampilan berpikir kritis peserta didik dalam menyelesaikan LKPD tergolong dalam kategori sangat baik.